Focusing of laser light by circular microcylinders with a metal shell. (2017) - Kozlova, E.S.; Kotlyar, V.V.
Abstract: Propagation of the TE-polarized light at a wavelength of λ=532 nm through a circular microcylinder from a polyester with a gold shell was simulated by using the finite difference method implemented in COMSOL Myltiphysics. The microcylinder radius was 2.1749λ and thickness of gold shell was 100 nm. The simulation showed the presence of a narrow nanojet with the maximum intensity in 6 times higher than the intensity of the incident light. The full width and depth of the nanojet at half maximum of intensity were 0.39λ (207 nm) and 0.72λ (383 nm), respectively. It was shown that using of thin metal shell can increase the nanojet length.